Performance Comparison Between HMLP, MLP And Recurrent Networks With Applications To Carbon Monoxide Concentrations Forecasting. - Raji, Usharani; Mashor, M Y; Adom, A H; Ali, A N; Sadullah, A F. (2005)

(untitled)
This paper compares the performance of Hybrid Multilayered Perceptron (HMLP) network, Multilayered Perceptron (MLP) network and Recurrent network. These networks are used to model and forecast carbon monoxide (CO) concentration.